Pronounced enhancement of .NO-dependent antimicrobial action by an .NO-oxidizing agent, imidazolineoxyl N-oxide. - Yoshida, K (1993)
The antimicrobial action of .NO against Cryptococcus neoformans was investigated by using imidazolineoxyl N-oxide, which we recently reported removes .NO via oxidation (T. Akaike, M. Yoshida, Y. Miyamoto, K. Sato, M. Kohno, K. Sasamoto, K. Miyazaki, S. Ueda, and H. Maeda, Biochemistry 32:827-832, 1993). No appreciable fungicidal activity was observed in neutral .NO solutions. Imidazolineoxyl N-oxide induced or enhanced fungicidal action in neutral or acidic .NO solutions, respectively. Our results provide convincing evidence that .NO is not a microbicidal molecular species.